KEANEKARAGAMAN JENIS TUMBUHAN BAWAH PASCAKEBAKARAN DI KAWASAN HUTAN LINDUNG LIANG ANGGANG - Dhea Qolbina; Udiansyah Udiansyah; Mochamad Arief Soendjoto (Jurnal Sylva Scienteae, 2026)
This research aims to analyze understory plant types, and analyze the Importance Value Index (INP) and Diversity Index (H') of understory plant types in post-fire areas in the Liang Anggang protected forest area. The method used in this research is observation with a purposive sampling technique to determine the location of research measuring plots. Measuring plots were made systematically with a length of 100 m in 3 lanes and consisting of 5 observation plots measuring 20 x 20 m, then subplots of 2 m x 2 m were made for grass types and subplots of 5 m x 5 m for seedlings and herbs. Plots are made in a zig-zag manner so that all vegetation can be represented. The Importance Value Index is determined from the relative density and relative frequency of a type. Diversity Index based on the Shannon Wiener index. The results of the research found 21 types of understory plants which were divided into 15 families with a total of 697 individuals belonging to grass, seedling and herb types, and one type of sapling. The type that has the highest Important Value Index for grass species is reeds (Imperata cylindrica) with a value of 106.49%. The type of seedlings and herbs that dominate or have the highest Importance Value Index is galam (Melaleuca leucadendron) at 71.24%. The diversity index for grass species obtained a value of 1.054, which is included in the medium category, and the diversity index for seedlings and herbs obtained a value of 1.089, which is also included in the medium category.